2004
DOI: 10.1590/s1806-83242004000400014
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among mutans streptococci counts, dental caries, and IgA to Streptococcus mutans in saliva

Abstract: Two-hundred and forty individuals were studied, divided into five groups as follows: caries-free children, children with caries, children with rampant caries, young adults with and without caries. Whole stimulated saliva was collected and all individuals were investigated for DMFT/dmft according to the WHO criteria and the simplified oral hygiene index (OHI-S). Quantitative analysis of the total aerobic flora and mutans streptococci in saliva was performed. Also, the level of salivary anti-S. mutans IgA was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 21 publications
(15 reference statements)
4
37
2
4
Order By: Relevance
“…The discrepancy in the results could be due to differences in the methodology. It is important to note that the use of purified antigens derived from cariogenic microorganisms is likely to provide a more reliable method for evaluating the contribution of salivary IgA to caries resistance [Bolton and Hlava, 1982] compared to analysis using nonpurified antigens and may explain the difference between our data and those of Koga-Ito et al [2004].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The discrepancy in the results could be due to differences in the methodology. It is important to note that the use of purified antigens derived from cariogenic microorganisms is likely to provide a more reliable method for evaluating the contribution of salivary IgA to caries resistance [Bolton and Hlava, 1982] compared to analysis using nonpurified antigens and may explain the difference between our data and those of Koga-Ito et al [2004].…”
Section: Discussionmentioning
confidence: 87%
“…While some studies show that high anti-MS antibody activity is associated with caries presence in children [de Farias and Bezerra, 2003;Koga-Ito et al, 2004], others show the opposite [Bolton and Hlava, 1982;Kirtaniya et al, 2009]. Moreover, the identification of factors involved in mutans streptococcal colonization could be a key point in the pathogenesis of ECC that can be targeted for caries prevention in early childhood.…”
mentioning
confidence: 99%
“…S. mutans is detected in a vast majority (>90%) of adults regardless of their country, race, sex, eating habits, or presence of dental caries [27]. Several clinical studies have reported a clear relationship between S. mutans levels in the saliva and the development of dental caries in populations with a relatively high risk of dental caries [42,43]. To evaluate caries risk in terms of the bacterial factor, it is important to evaluate not only the total amount of S. mutans and S. sobrinus, but also the amounts of each.…”
Section: Discussionmentioning
confidence: 99%
“…Karyojenik mikroorganizmaların diş sert yüzeylerine adezyonunu önlemekte ve glikoziltransferaz aktivitesini inhibe edebilmektedir. 25,26 Salgısal IgA'nın sentez ve salgılanmasının dü-zenlenmesi antijenik uyarılmanın yanında nöroen-dokrin kontrole de bağlıdır. 27 Bu durumda stres, egzersiz, hamilelik, menstrüel döngü ve farmakolojik müdahaleler de tükürük IgA seviyesini etkileyebilmektedir.…”
Section: Anti̇bakteri̇yel Protei̇nlerunclassified